Validation of a Preparation for Decision Making scale - Bennett, Carol; Graham, Ian D.; Kristjansson, Elizabeth; Kearing, Stephen A.; Clay, Kate F.; O’Connor, Annette M. (Patient education and counseling, 2010)
The Preparation for Decision Making (PrepDM) scale was developed to evaluate decision processes relating to the preparation of patients for decision making and dialoguing with their practitioners. The objective of this study was to evaluate the scale's psychometric properties. From July 2005 to March 2006, after viewing a decision aid prescribed during routine clinical care, patients completed a questionnaire including: demographic information, treatment intention, decisional conflict, decision aid acceptability, and the PrepDM scale. Four hundred orthopaedic patients completed the questionnaire. The PrepDM scale showed significant correlation with the informed ( r = −0.21, p < 0.01) and support ( r = −0.13, p = 0.01) subscales (DCS); and discriminated significantly between patients who did and did not find the decision aid helpful ( p < 0.0001). Alpha coefficients for internal consistency ranged from 0.92 to 0.96. The scale is strongly unidimensional (principal components analysis) and Item Response Theory analyses demonstrated that all ten scale items function very well. The psychometric properties of the PrepDM scale are very good. The scale could allow more comprehensive evaluation of interventions designed to prepare patients for shared-decision making encounters regarding complex health care decisions.